Factors associated with refeeding hypophosphatemia in adolescents and young adults hospitalized with anorexia nervosa. (8th September 2021) - Kells, Meredith; Gregas, Matt; Wolfe, Barbara E.; Garber, Andrea K.; Kelly‐Weeder, Susan
Abstract: Background: Refeeding hypophosphatemia (RH) in individuals with anorexia nervosa (AN) is a potentially fatal complication of nutrition restoration; yet, little is known about risk. This retrospective cohort study examined factors found in hospitalized youth with AN that may contribute to RH. Methods: We reviewed medical records of 300 individuals diagnosed with AN admitted between the years of 2010 and 2016. Logistic regression examined factors associated with RH. Multivariate regression examined factors associated with phosphorus nadir. Results: For 300 participants, the mean (SD) age was 15.5 (2.5) years, 88.3% were White, and 88.3% were female. Participants lost an average of 11.3 (9.7) kg of body weight and were 82% (12.1) of median body mass index (BMI). Age ( P = .022), nasogastric (NG) tube feeding ( P = .054), weight gain ( P = .003), potassium level (P = .001), and magnesium level ( P = .024) were contributors to RH. Odds of RH were 13.7 times higher for each unit reduction in magnesium, 9.2 times higher for each unit reduction in potassium, three times higher in those who received NG feeding, 1.5 times higher for each kg of weight gain, and 1.2 times higher for each year of age. Regarding phosphorus nadir, serum magnesium level ( P < .001) and admission BMI ( P = .002) contributed significantly. Conclusion: The results indicate that age, NG feeding, weight gain, electrolyte abnormalities, and BMI on admission are potential indicators of the development of RH in youth. This study identifies clinical risk factors associated with RH and may guide further investigation.